Disease Characteristics and Severity in Patients With Inflammatory Bowel Disease With Coexistent Diabetes Mellitus. Issue 9 (16th January 2020) - Din, Hassieb; Anderson, Alyce J; Ramos Rivers, Claudia; Proksell, Siobhan; Koutroumpakis, Filippos; Salim, Tariq; Babichenko, Dmitriy; Tang, Gong; Koutroubakis, Ioannis E; Schwartz, Marc; Johnston, Elyse; Barrie, Arthur; et al.
Abstract : We sought to characterize the effects of diabetes mellitus on the natural history of inflammatory bowel disease. From a large cohort of inflammatory bowel disease patients, we found that although patients suffering from comorbid diabetes mellitus demonstrated evidence of increased disease severity, they may be undertreated with immunomodulator and/or biologic agents. Abstract: Background: Given the rising prevalence of diabetes mellitus (DM) and the limited data on its effect on the course of inflammatory bowel disease (IBD), we characterized multiyear patterns of disease severity in a cohort of IBD patients with coexistent DM. Methods: Data of consented IBD patients followed prospectively in a natural history registry at a tertiary center between 2009 and 2017 were analyzed. Patients with ≥3 years of clinical follow-up were included. Patients identified with a diagnosis of DM were compared with 400 consecutive IBD controls without a diagnosis of DM, no laboratory evidence of hyperglycemia, and no history of antihyperglycemic treatment. Results: Out of 2810 IBD patients, 141 (5%) had DM (IBD DM; 44% ulcerative colitis, 56% Crohn's disease, 48.2% female). IBD DM had higher use of 5-aminosalicylic acid (5ASA) agents ( P = 0.04), narcotics ( P < 0.001), and antibiotics ( P = 0.007) but not immunomodulators and/or biologics compared with IBD controls. When analyzing biomarkers of severity, IBD DM demonstrated higher frequencies of elevated C-reactive protein (CRP; P = 0.006), elevated erythrocyte sedimentation rate (ESR; P = 0.001), eosinophilia ( P = 0.004), monocytosis ( P = 0.02), and hypoalbuminemia ( P = 0.001). IBD DM had worse quality of life (mean Short Inflammatory Bowel Disease Questionnaire; P < 0.001). IBD DM had increased health care utilization compared with controls (emergency room usage P = 0.008, hospitalizations P < 0.001, gastroenterology clinic visits P < 0.001, and median annual charges P < 0.001). Among IBD DM patients, the use of immunomodulators and/or biologics was not associated with further complications as measured by antibiotic use or hospitalizations. Conclusions: This study of a large IBD cohort suggests that DM in IBD may be associated with increased disease severity and that there may be room for increasing use of highly effective immunomodulator and/or biologic agents in this group. Video Abstract: